2022
DOI: 10.1111/aas.14025
|View full text |Cite
|
Sign up to set email alerts
|

The role of mechanical ventilation in primary graft dysfunction in the postoperative lung transplant recipient: A single center study and literature review

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…There were 3/11 studies that reported the association between tidal volume and PGD grade within the first 72 h 9,10,15 . Two of the studies identified no significant association 9,15 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There were 3/11 studies that reported the association between tidal volume and PGD grade within the first 72 h 9,10,15 . Two of the studies identified no significant association 9,15 .…”
Section: Resultsmentioning
confidence: 99%
“…The positive‐end expiratory pressure (PEEP) was reported in 8/11 studies with a range from 5 to 12 cmH 2 O 9–15,18 . The method of PEEP selection was reported in 1/11 studies, which included initial PEEP selection based on a protocol 9 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations